Excel 2007 PivotTables Recipes A Problem-Solution Approach - Dalgleish, Debra (Apress : Imprint: Apress, 2007)
Debra Dalgleish, Microsoft Office Excel "Most Valuable Professional" since 2001, and an expert and trainer in Excel, brings together a one-stop resource for anyone curious about representing, analyzing, and using their data with PivotTables and PivotCharts. You'll find this book inimitable when facing any new or difficult problem in PivotTables, covering the entire breadth of situations you could ever encounter, from planning and creating, to formatting and extracting data, to maximizing performance and troubleshooting. The author presents tips and techniques in this collection of recipes that can't be found in Excel's Help section, while carefully explaining the most confusing features of PivotTables to help you realize their powerful potential. The chapters in this book have been organized into a collection of recipes to take you step by step from the problem you are experiencing to the solution you are aiming for. Without fuss, you'll find clear and precise information to help you assess your situation, whether common or unique, and solve your problem. Working examples of complex PivotTables and numerous PivotTable programming examples will help you solve problems quickly, without the need to digest heavy content.